Midwifery Practice: Analisis Of Implementation Of Prenatal Education Classes Program In Semarang City - Sri Sumarni; Sri Wahyuni; Sri Rahayu (Poltekkes Kemenkes Semarang, 2012)
This study is a qualitative research, using fenomenology approach. The data was collected by deep interview method. There are four variables contributed in this study which are communication, resourcers, disposition or motivation of implementor, and bereaucratic structure.There are 8 midwives as an informant involving in this study. The result of this study shows that informant are 32 until 57 years old, the length of working experience for 12 until 37 years, and graduated from D 3 dan 4 of midwifery program. All of midwives have been exposured of antenatal education classes training. The classes have been diseminated by Primary Health Service and Hospital by putting announcement on board. Structures of Organisation were not completely yet in Primary Health Service nor in Hositals. On the other hand, there are no found a structure of antenatal education classes organisation at an independent midwives.